2007
DOI: 10.1007/s10856-007-3031-8
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for the measurement of mechanical properties of bone by nanoindentation

Abstract: Nanoindentation is widely used to measure the mechanical properties of bio-tissues. However, viscoelastic effects during the nanoindentation are seldom considered rigorously, although they are in general very significant in bio-tissues. In this study, a recently developed method for correcting the viscoelastic effects during nanoindentation is applied to mice bone samples. This method is found to yield reliable elastic modulus and hardness results from forelimb and femur cortical bone samples of C57 BL/6N and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 31 publications
(75 reference statements)
1
27
0
Order By: Relevance
“…As evaluations performed using nanoDMA involve both a quasi-static and dynamic loading component, there are potential contributions of the loading protocol on the responses. Also, previous work has shown that nanoindentation responses of bone are a strong function of loading rate and viscous effects [Fan and Rho, 2003; Bembey et al, 2006; Tang et al, 2007]. To the author’s knowledge no investigation has explored the application of nanoDMA to evaluate the parametric dependence in mechanical behavior of dentin under dynamic loading, or the differences between hydrated intertubular and peritubular dentin.…”
Section: Introductionmentioning
confidence: 99%
“…As evaluations performed using nanoDMA involve both a quasi-static and dynamic loading component, there are potential contributions of the loading protocol on the responses. Also, previous work has shown that nanoindentation responses of bone are a strong function of loading rate and viscous effects [Fan and Rho, 2003; Bembey et al, 2006; Tang et al, 2007]. To the author’s knowledge no investigation has explored the application of nanoDMA to evaluate the parametric dependence in mechanical behavior of dentin under dynamic loading, or the differences between hydrated intertubular and peritubular dentin.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoindentation has been employed to characterize local mechanical properties of bone (Fan et al, 2002;Hengsberger et al, 2003;Hoffler et al, 2005;Oliver and Pharr, 1992;Oyen, 2006;Rho et al, 2001Rho et al, , 1997;Swadener et al, 2001;Tai et al, 2005;Tang et al, 2007;Ulm et al, 2007;Zebaze et al, 2011;Zysset et al, 1999). Several factors can affect the measured properties of bone: species type, tissue type, age, sample orientation, anatomical location, collagen orientation and degree of mineralization, and these have been studied by nanoindentation as reviewed by Lewis and Nyman (2008); Thurner (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, corrections for viscoelasticity are needed to avoid errors in the computed values of the nanomechanical properties. Tang et al 8,9 have presented a method for correcting for viscoelastic effects when bone tissue specimens are tested. The method involves assuming a Maxwell law-type viscoelastic model to derive the real elastic contact stiffness, S e , and substituting S e for S u in Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic Viscosity, g. Tang et al 8 have presented a method for computing g and applied it to bone tissues of mice, determining g of femur bone samples from two C57/ 6N mice and one ICR mouse to be (11.6 6 5.5) 39 presented the creep data as the relative penetration depth (the difference between the initial depth at the beginning of the hold period and the increasing depth during the hold period at P max ) versus time. There was a distinction in these results between dehydrated and rehydrated specimens.…”
mentioning
confidence: 99%